2019
DOI: 10.1177/0954405419889204
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimizing of cutting force and surface roughness in milling process of Inconel 738 using hybrid ANN and GA

Abstract: Super-alloys have high thermal and mechanical strength and are widely used for heat exchangers, turbine blades, and other parts which work under severe creep conditions. Machinability of these alloys is directly affected by mechanical and physical properties. In addition, cutting force and surface roughness are two important factors in machinability of alloys. Hence, numerous studies have been conducted in order to illustrate their influences. However, among these alloys, the machining of Inconel 738 has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 37 publications
0
25
0
1
Order By: Relevance
“…The encountered discontinuous chips result in preventing tool wear and accelerate the life of the tool which significantly increases the machined surface quality of the work material. 21,40 With the influence of high-speed machining of hard-to-cut materials, the heat generation will increase and accordingly results in decrease of plastic deformation and significantly decreasing the friction due to increment of temperature. 41 The cutting fluid applied along the flank face takes away the high heat generation and accordingly increases lubrication effect at the rake face of the cutting tool.…”
Section: Resultsmentioning
confidence: 99%
“…The encountered discontinuous chips result in preventing tool wear and accelerate the life of the tool which significantly increases the machined surface quality of the work material. 21,40 With the influence of high-speed machining of hard-to-cut materials, the heat generation will increase and accordingly results in decrease of plastic deformation and significantly decreasing the friction due to increment of temperature. 41 The cutting fluid applied along the flank face takes away the high heat generation and accordingly increases lubrication effect at the rake face of the cutting tool.…”
Section: Resultsmentioning
confidence: 99%
“…Hanafi et al 5 also employed the ANN method in predicting the cutting forces for the turning processes of carbon fiber-reinforced polymer composites. Imani et al 6 also adopted an ANN algorithm combined with experimental data to build a prediction model for investigating the cutting forces and surface roughness for machining Inconel 738, as well as optimizing the processing parameters with the genetic algorithm (GA). Moreover, Cus et al 7 used the ANN algorithms to effectively develop the cutting forces estimation models of ball-end milling processes.…”
Section: Introductionmentioning
confidence: 99%
“…The interpolative models of the SCE, arithmetical mean roughness (Ra), and means roughness depth (Rz) were developed in terms of the spindle speed (S), nose radius (r), f, and a for the dry milling of SKD61 material [4]; and the findings showed that a set of feasible optimal solutions could be employed to obtain a low SCE, a smooth surface, and high MRR. The artificial neural network (ANN) was applied to develop the models of the machining force (Fc) and SR regarding the axial depth of cut (ap), v, and f for the milling of Inconel 738 [5];…”
Section: Introductionmentioning
confidence: 99%